PENGARUH CITRA MEREK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK MICELLAR WATER GARNIER DI KOTA SURABAYA - Hernanda Julia Ayu Maharani; Ugy Soebiantoro (JURNAL LENTERA BISNIS, 2026)
The increasing competition in the skincare industry and the high demand for facial care products are driving cosmetic companies to build a strong brand image and set prices that align with consumer perceptions. Garnier, as one of the skincare brands, faces competition in maintaining consumer purchasing decisions for its Micellar Water products. Using a Likert-scale questionnaire and analyzed using the partial least squares (PLS) method, brand image and price perceptions influenced purchasing decisions for Garnier Micellar Water in Surabaya. This study employed a quantitative method with purposive sampling of 110 respondents aged at least 17. The study demonstrated that brand image and price perceptions have a positive and significant effect on purchasing decisions. The better the brand image and the more positive consumer perceptions of price, the higher the consumer's purchasing decision for Garnier Micellar Water.